Novel Route to Cationic Palladium(II)–Cyclopentadienyl Complexes Containing Phosphine Ligands and Their Catalytic Activities - Dmitry S. Suslov; Mikhail V. Bykov; Marina V. Pakhomova; Timur S. Orlov; Zorikto D. Abramov; Anastasia V. Suchkova; Igor A. Ushakov; Pavel A. Abramov; Alexander S. Novikov (Molecules, 2023)
The Pd(II) complexes [Pd(Cp)(L)n]m[BF4]m were synthesized via the reaction of cationic acetylacetonate complexes with cyclopentadiene in the presence of BF3∙OEt2 (n = 2, m = 1: L = PPh3 (1), P(p-Tol)3, tris(ortho-methoxyphenyl)phosphine (TOMPP), tri-2-furylphosphine, tri-2-thienylphosphine; n = 1, m = 1: L = dppf, dppp (2), dppb (3), 1,5-bis(diphenylphosphino)pentane; n = 1, m = 2 or 3: 1,6-bis(diphenylphosphino)hexane). Complexes 1–3 were characterized using X-ray diffractometry. The inspection of the crystal structures of the complexes enabled the recognition of (Cp–)⋯(Ph-group) and (Cp–)⋯(CH2-group) interactions, which are of C–H…π nature. The presence of these interactions was confirmed theoretically via DFT calculations using QTAIM analysis. The intermolecular interactions in the X-ray structures are non-covalent in origin with an estimated energy of 0.3–1.6 kcal/mol. The cationic palladium catalyst precursors with monophosphines were found to be active catalysts for the telomerization of 1,3-butadiene with methanol (TON up to 2.4∙104 mol 1,3-butadiene per mol Pd with chemoselectivity of 82%). Complex [Pd(Cp)(TOMPP)2]BF4 was found to be an efficient catalyst for the polymerization of phenylacetylene (PA) (catalyst activities up to 8.9 × 103 gPA·(molPd·h)−1 were observed)